Efecto de goma tragacanto, cloruro de magnesio y tiempo de ultrasonido en la protección de vitamina C en pulpa de chalarina (Casimiroa edulis L.) - Amador Fernández, Santos Ignacio (2019)
The objective of the present work was to evaluate the effect of the application of tragacanth gum (polymer), magnesium chloride (salt) and ultrasound degassing time at 40 kHz on the stability of vitamin C in the solution of pulp of chalarina (Casimiroa edulis L.) pasteurized using the response surface methodology. The raw material came from the District of Huamachuco and the determination of vitamin C was carried out by titration with 2,6- dichlorophenolindophenol. A DCCR factorial design was proposed with 17 treatments (2k + 2k + pc) whose independent variables were tragacanth gum (0 – 5% w/w), magnesium chloride (0 - 1% w/w) and degassing time (0 - 10 minutes). Through modeling the equation was obtained that relates the content of ascorbic acid (Y) with the independent variables (X1: tragacanth gum concentration, X2: MgCl2 and X3: degassing time): = 3.6828 + 0.7556 ∗ 1 − 0.1255 ∗ 1 2 + 15.0434 ∗ 2 − 8.8332 ∗ 2 2 + 3.8140 ∗ 3 − 0.1834 ∗ 3 2 + 1.1812 + 0.011313 − 2.246723. The analysis of variance showed statistically significant effect (p <0.05) on the part of the variables in a linear way as quadratic; except for part of X1 quadratically and the interactions X1X2 and X1X3. Likewise, greater protection was achieved in the content of vitamin C in the solution of pasteurized pulp, at the values of 3 - 4% w / w of tragacanth gum, 0.2 - 0.3% w/w of magnesium chloride and 6 - 8 minutes of degassing.